Strategi Pengembangan Bisnis Melalui Analisis SWOT pada Usaha Patricia Accecories di Maumere - Emiliano Eo Kutu Go’o; Frederika Susanti; Maria Atris Wolo; Elisabeth Fidella; Patricia Matilda Tina; Robertus Mario Uje (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze business development strategies through a SWOT analysis approach for Patricia Aksesoris, focusing on understanding the internal and external conditions that influence business development. The analysis results show that Patricia Aksesoris has strengths in good product quality and a variety of attractive designs. However, this business also faces weaknesses, such as limitations in promotion and capital that can limit expansion. Opportunities that can be exploited include the growing trend in accessories and the great potential for marketing through digital platforms. On the other hand, the main threats faced are intense price competition and rapid changes in consumer tastes. Based on these findings, the recommended strategies to increase business competitiveness are strengthening marketing through social media, improving customer relationships, and improving operational management to achieve greater efficiency. With these strategies, Patricia Aksesoris can strengthen its position in the market and achieve sustainable growth.